Genotype-phenotype correlation in Taiwanese children with diazoxide-unresponsive congenital hyperinsulinism - Lee, Cheng-Ting; Tsai, Wen-Hao; Chang, Chien-Ching; Chen, Pei-Chun; Fann, Cathy Shen-Jang; Chang, Hsueh-Kai; Liu, Shih-Yao; Wu, Mu-Zon; Chiu, Pao-Chin; Hsu, Wen-Ming; Yang, Wei-Shiung; Lai, Ling-Ping; et al. (Frontiers in Endocrinology, 2023)
Objective: Congenital hyperinsulinism (CHI) is a group of clinically and genetically heterogeneous disorders characterized by dysregulated insulin secretion. The aim of the study was to elucidate genetic etiologies of Taiwanese children with the most severe diazoxide-unresponsive CHI and analyze their genotype-phenotype correlations. Methods: We combined Sanger with whole exome sequencing (WES) to analyze CHI-related genes. The allele frequency of the most common variant was estimated by single-nucleotide polymorphism haplotype analysis. The functional effects of the ATP-sensitive potassium (KATP) channel variants were assessed using patch clamp recording and Western blot. Results: Nine of 13 (69%) patients with ten different pathogenic variants (7 in ABCC8, 2 in KCNJ11 and 1 in GCK) were identified by the combined sequencing. The variant ABCC8 p.T1042QfsX75 identified in three probands was located in a specific haplotype. Functional study revealed the human SUR1 (hSUR1)-L366F KATP channels failed to respond to intracellular MgADP and diazoxide while hSUR1-R797Q and hSUR1-R1393C KATP channels were defective in trafficking. One patient had a de novo dominant mutation in the GCK gene (p.I211F), and WES revealed mosaicism of this variant from another patient. Conclusions: Pathogenic variants in KATP channels are the most common underlying cause of diazoxide-unresponsive CHI in the Taiwanese cohort. The p.T1042QfsX75 variant in the ABCC8 gene is highly suggestive of a founder effect. The I211F mutation in the GCK gene and three rare SUR1 variants associated with defective gating (p.L366F) or traffic (p.R797Q and p.R1393C) KATP channels are also associated with the diazoxide-unresponsive phenotype.